Analisis Literasi Matematika Soal HOTS Ditinjau dari Kemandirian Belajar Siswa Kelas X SMA - Rahmayanti, Erli; Sukestiyarno, YL; Zaenuri, Zaenuri (Universitas Muria Kudus, 2023)
Literacy is a human right and the basis for lifelong learning covering various aspects of life. One of these aspects is the need for mathematical literacy. The 21st century learning system, Indonesian education does not only focus on 4C skills, but there is development of these skills, namely students' skills in dealing with HOTS (higher order thinking skills) questions. Mathematics literacy regarding HOTS questions at SMA/MA/SMK level is still low, one of the causes is the lack of student learning independence. The aim of this research is to describe the mathematics literacy of HOTS questions in terms of student learning independence. This type of research is a case study with a descriptive qualitative approach. The research subjects consisted of three class X students where each student represented each category of learning independence, namely: low, medium and high. Data collection uses questionnaires, tests and interviews. The research results showed that (1) students with low learning independence were only able to master the indicators of identifying problems and making conclusions; (2) students with moderate learning independence were quite good at mastering the indicators of mathematics literacy but did not master the indicators of finding solutions to problems; and (3) students with high learning independence are able to master all indicators of mathematics literacy. Therefore, the high level of student learning independence significantly influences students' mathematics literacy abilities.